Shifts in Patronage Differentiation: Translation from European Languages in Isolationist Japan - Hadley, James (Meta, 2016)
This article demonstrates that translation patronage can shift imperceptibly between being undifferentiated and differentiated. It focuses on the passage of time as a factor that could be added to Lefevere’s conceptualization of patronage. Currently this conceptualization approaches history as a series of snapshots, with little focus on transition, most importantly, between one form of patronage and another. With an overview of the development of translation patronage in early modern Japanese history, this article explores the dynamics of translation patronage over a period of well over two centuries, when the country maintained a policy of national isolationism. Under this policy, Christianity became absolutely taboo, and those associated with it were regarded with utmost suspicion. Yet, limited international trade was permitted to continue by a state-owned collegium of interpreters. Under this system, the patronage of translators in Japan was extremely undifferentiated, being obtained solely from governmental sources. However, before the end of this system, patronage had already shifted to a differentiated model, in which translation services were being sought by a wide range of parties beyond the government.